2022
DOI: 10.3390/ijerph19031528
|View full text |Cite
|
Sign up to set email alerts
|

Dental Emergency Admissions in Emergency Oral Health Care Centers during COVID-19 Pandemic in Buenos Aires, Argentina

Abstract: This study aimed to describe patients’ demographic characteristics and treatment delivered in private and public dental emergency clinics and to compare them with a pre-pandemic period. A retrospective cross-sectional study was carried out on patients attending the University Dental Hospital of the University of Buenos Aires and on one private dental clinic, situated in Buenos Aires, between March and June of 2019 and 2020. The sample considered all the patients’ medical records of those requiring emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This review did not include dental care, so there are no studies yet showing the impact of the pandemic on dental care in national health services. To date, reports are available on the impact of the COVID-19 pandemic on specific community dental services (Rodriguez et al, 2022;Shah et al, 2022) or in high-risk patient groups (O'Donnell et al, 2022) and seniors (Weber et al, 2022). A study in Australia, conducted with care records from four of the six national states, showed a 52% decrease in care from March to May 2020 in pediatric dental care, then recovering to pre-pandemic levels of care (Hopcraft and Farmer, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This review did not include dental care, so there are no studies yet showing the impact of the pandemic on dental care in national health services. To date, reports are available on the impact of the COVID-19 pandemic on specific community dental services (Rodriguez et al, 2022;Shah et al, 2022) or in high-risk patient groups (O'Donnell et al, 2022) and seniors (Weber et al, 2022). A study in Australia, conducted with care records from four of the six national states, showed a 52% decrease in care from March to May 2020 in pediatric dental care, then recovering to pre-pandemic levels of care (Hopcraft and Farmer, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dental services were used differently during COVID-19, according to several studies [ 14 , 15 , 16 , 17 ]. Emergency dental visits were shown to be on the rise in certain studies [ 14 , 15 , 18 , 19 ], whereas others [ 20 ] found no discernible increase in these visits. Information on how the COVID-19 pandemic has affected the use of dental emergency care is scarce.…”
Section: Introductionmentioning
confidence: 99%